Endüstri 4.0 Kapsamında Dijital Gazete İşletmelerinin Sürdürülebilir Rekabet Stratejileri. - Demircioğlu, Esma Ahsen; Onar, Sinem (Electronic Turkish Studies)
In the contemporary era, the constant renewal, updating, and advancement of technology is frequently emphasized in the literature. Digitalization, driven by technological advancements, affects all aspects of life, transforming not only economic processes but also societal structures. Historically, the press, serving the public's need for information, has been directly influenced by industrial revolutions, economic changes, and emerging digital processes, and continues to evolve in this direction. Compared to traditional newspaper enterprises, digital newspaper enterprises leverage the opportunities provided by the internet and web technologies to adapt to technological tools, reach wider audiences, and maintain their presence in increasingly competitive markets. Consequently, practices of utilizing technology, developing technologydriven business strategies, and formulating competitive strategies have become prominent. Digital newspaper enterprises aim to differentiate themselves, build a loyal audience base, and create sustainable revenue models to counteract the challenges of increasing and diversifying competition. In this context, the concept of Industry 4.0 signifies the integration of technology with production, involving smart technologies in the production process to enhance efficiency. This phenomenon not only facilitates advancements in information technologies but also significantly impacts the press industry. This study focuses on whether the strategies adopted by digital newspaper enterprises for sustainable competitive advantage within the framework of Industry 4.0 are technology-oriented, whether technology utilization practices are prioritized in these competitive strategies, how they adapt to new journalism practices emerging under Industry 4.0, and how their perspectives on the transition from traditional to digital journalism activities reflect these changes. Furthermore, it explores the transformations in digital journalism practices and their impact on competitive strategies. This study is derived from the master's thesis titled “Dijital Gazete İşletmelerinde Sürdürülebilir Rekabet Üstünlüğü Bağlamında Endüstri 4.0” Ethical approval for the study was obtained from the ethics committee (decision no. 1622 dated 28.09.2022). The research employed a purposive sampling method, targeting 18 local digital newspaper enterprises in İzmir, which are both traditionally and digitally active and subject to the Press Advertisement Agency regulations. Data was collected using a semi-structured in-depth interview technique, and the findings were interpreted through content analysis.